High-strength and high-toughness tungsten-based composite material and preparation method thereof
By adopting a combination of multi-end point mesh structure, nanoparticles and tungsten powder in tungsten composite materials, the problem of insufficient strength and toughness of tungsten composite materials is solved, high strength and toughness and improved brittleness are achieved, and its application capabilities in high temperature and irradiation environments are enhanced.
Patent Information
- Application Number
- CN202510070239.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-16
AI Technical Summary
Existing tungsten-based composite materials have problems of insufficient strength and toughness, especially in high temperature and irradiated environments, which limits their application.
Using a combination of multi-end point mesh structure, nanoparticles and tungsten powder, the structural design of main branch fibers, branched fibers and bridged fibers is combined with the uniform dispersion of nanoparticles and the high density of tungsten powder to form a high-strength and tough tungsten composite material.
It significantly improves the strength and toughness of tungsten-based composite materials, improves its brittleness, and enhances its application capabilities in high temperature and irradiated environments.
Smart Images

Figure CN119843134A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite material preparation, and in particular relates to a high-strength and toughness tungsten-based composite material and a preparation method thereof. Background Art
[0002] Tungsten (W) is a material with a high atomic number and high density (19.35 g / cm 3 ), high melting point (3412℃), high hardness, excellent corrosion resistance, and electrical and thermal conductivity, etc., and are widely used in many fields such as energy, aerospace, national defense, military, automobile industry, and medical machinery. In the field of energy, tungsten is one of the most promising materials for plasma materials in nuclear fusion reactors. However, the brittleness of tungsten materials is its obvious defect. The ductile-to-brittle transition temperature (DBTT) is one of the indicators to measure the brittleness and toughness of tungsten and tungsten-based materials. It refers to the temperature at which tungsten materials change from ductile fracture to brittle fracture. For tungsten, this temperature is relatively high, because tungsten itself is a body-centered cubic (BCC) structured metal. The electronic structure, atomic bond characteristics, and lattice resistance of the dislocation stress field of BCC metals determine the room temperature brittleness of tungsten. In addition, the recrystallization brittleness and radiation embrittlement of tungsten severely limit the application of tungsten materials in service environments such as irradiation and high temperature.
[0003] At present, there are two main effective methods to improve the toughness of tungsten materials: internal toughening method and external toughening method. The internal toughening method mainly improves the plasticity of tungsten by adding alloying elements (such as rhenium, molybdenum, copper, etc.), second phase particles or refining tungsten grains to tungsten. However, due to the high strength of tungsten itself and its sensitivity to impurities, as well as the easy occurrence of recrystallization in a high heat load service environment, the effect of using the internal toughening method alone is not obvious; the external toughening method is toughened by adding tough phases such as fibers and layered materials to the tungsten matrix, which is called fiber toughening and layered toughening. Layered toughened tungsten-based composite materials generally combine some tough metal foils, such as titanium foil, vanadium foil, tantalum foil and copper foil, with tungsten foil through rolling welding, diffusion bonding and other methods to form a multi-layer organization and heterogeneous metal interface structure. The toughening phases of fiber toughening include metal fibers, carbon fibers and tungsten fibers. However, the current fiber toughening still has defects such as low density of composite materials, poor interface bonding, and easy occurrence of micropores and cracks in composite materials, which affect the overall performance of tungsten-based composite materials. For example, a Chinese patent with the authorization announcement number CN112442643 B discloses a layered fiber-toughened tungsten-based composite material and a preparation method thereof, wherein the composite material comprises a tungsten matrix layer and a titanium foil and a tungsten fiber mesh toughening layer alternately stacked on each other, and the layered fiber-toughened tungsten-based composite material is obtained by spark plasma sintering under vacuum conditions. However, the tungsten-based composite material obtained by this method lacks an interface between the collective layer and the toughening layer, which is not conducive to improving the fracture dissipation energy. Summary of the invention
[0004] The technical problem to be solved by the present invention is that the current tungsten-based composite materials still have the problem of insufficient strength and toughness. The purpose is to provide a high-strength and toughness tungsten-based composite material and a preparation method thereof, which can improve the brittleness of the tungsten-based composite material and improve the toughness of tungsten.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A high-strength and toughness tungsten-based composite material includes a multi-end reticular structure, nanoparticles and a matrix material. The multi-end reticular structure includes main branch fibers, branch fibers and bridging fibers; in the multi-end reticular structure, adjacent main branch fibers are connected to each other through bridging fibers, and the branch fibers are distributed on the main branch fibers; the nanoparticles include non-magnetic nanoparticles and magnetic nanoparticles, which are uniformly distributed in the multi-end reticular structure; and the matrix material is tungsten powder.
[0007] Fiber toughening belongs to the external toughening method. Its basic principle is to use the high strength and high modulus characteristics of the fiber to disperse and absorb the stress originally acting on the matrix material. The fiber can disperse the stress to a larger area, reduce stress concentration, and thus reduce the generation and expansion of cracks. After the crack is generated, the fiber will produce a certain closing pressure on the crack surface. This pressure makes the crack tend to close, hindering the opening and continued extension of the crack. The fiber in the tungsten-based composite can also change the direction of crack expansion and play a role in crack deflection. When the crack propagation encounters the fiber, due to the presence of the fiber, the crack cannot continue to expand in a straight line in the original direction. The fiber is like a barrier, forcing the crack to change direction, making the crack expansion path tortuous, and the crack needs to overcome more obstacles and consume more energy, thereby improving the toughness of the material.
[0008] As the main load-bearing structure in the toughening unit, the main branch fiber provides the basic strength and rigidity for the tungsten-based composite material. The main branch fiber bears most of the mechanical loads in the composite material, including tensile, compressive and bending loads. The main branch fiber can effectively transfer the various mechanical loads from one end of the fiber to the other end, thereby reducing local stress concentration. The branch fibers are distributed on the main branch fibers to form a branch structure. This structure makes the crack propagation path more complicated, so that more energy is consumed to propagate the crack, which improves the fracture toughness of the material. The branch fibers can also play a bridging role near the crack tip to prevent the rapid expansion of the crack. Different branch structures are connected to each other by bridging fibers to form a multi-end quasi-net structure, which not only significantly increases the complexity of the crack path, but the bridging fibers themselves can also provide additional energy absorption mechanisms, further improving the overall toughness of the tungsten-based composite material.
[0009] Nanoparticles have a huge specific surface area and can fill the gaps between fibers, which can significantly improve the density of tungsten-based composite materials and improve the bonding strength between tungsten fibers and tungsten matrix. When the interfacial bonding strength between the fiber and the tungsten matrix is moderate, cracks can extend along the interface between the fiber and the tungsten matrix, and the fiber can undergo plastic deformation before breaking, thereby absorbing a large amount of energy, thus playing a toughening role. Nanoparticles can also prevent crack extension through the pinning effect.
[0010] As a matrix material, tungsten powder provides the basic physical and chemical properties of tungsten-based composites and is also the basis of the strength and hardness of composites.
[0011] Preferably, the main branch fiber is a long tungsten fiber with a length of 10 to 50 mm, a diameter of 80 to 300 μm, and a mass ratio of 24 to 36%; the branch fiber is a short tungsten fiber with a length of 1 to 3 mm, a diameter of 30 to 100 μm, and a mass ratio of 8 to 12%; the bridging fiber is an alumina fiber with a fiber length of 16 to 28 mm, a diameter of 50 to 200 μm, and a mass ratio of 15 to 20%. Tungsten fiber is selected as the material for the main branch fiber and the branch fiber because tungsten fiber does not need to introduce other alloy elements, and the toughness of the tungsten-based composite material is improved by giving full play to the excellent properties of the fiber itself. The main branch fiber is a long tungsten fiber, and the branch fiber is a short tungsten fiber. The present invention uses alumina fiber as the bridging fiber. Alumina fiber also has excellent mechanical properties, including high strength and high modulus. These properties enable alumina fiber to effectively enhance the toughness and impact resistance of tungsten-based composite materials. Alumina fiber has extremely high chemical stability and thermal stability, with a melting point of up to 1840°C. It can be used at high temperatures of 1300 to 1400°C for a long time and maintain its structure and performance, thereby improving the high temperature resistance of tungsten-based composite materials. Compared with traditional metal materials, alumina fiber has a lower density, which helps to reduce the overall weight of tungsten-based composite materials.
[0012] Preferably, the nanoparticles are Al 2 O 3 Any one of nanoparticles, ZrC nanoparticles and TiC nanoparticles; the particle size of the nanoparticles is 25-60nm, and the mass ratio is 0.2-1.8%; the magnetic nanoparticles are nickel nanoparticles, and the particle size of the nickel nanoparticles is 10-20nm, and the mass ratio is 0.1-0.5%.
[0013] Al 2 O 3 Both Al nanoparticles and TiC nanoparticles have the characteristics of high hardness. They can be evenly dispersed in the toughening unit to form hard points, reduce wear during friction, and significantly improve the hardness and wear resistance of tungsten-based composite materials. 2 O 3 Nanoparticles also have good thermal stability, can maintain their structure and function in high temperature environments, and improve the high temperature resistance of composite materials. TiC nanoparticles can maintain good stability in corrosive environments, thereby improving the corrosion resistance of composite materials. ZrC nanoparticles have high fracture toughness, and are not prone to brittle fracture when tungsten-based composite materials are impacted by external forces. ZrC nanoparticles can also form a stable oxide layer under high temperature conditions, thereby protecting the interior of the composite material from further oxidation and extending the service life of the composite material.
[0014] Nickel is a metal with good plasticity and toughness, good oxidation resistance, a melting point of about 1455°C, and stable processing performance. When added in the form of nanoparticles, it can alleviate stress concentration to a certain extent and improve the fracture toughness of the composite material. Under the action of a magnetic field, nickel nanoparticles can arrange their magnetic moments as the magnetic field changes, and are distributed between non-magnetic nanoparticles to form microchannels.
[0015] Preferably, the tungsten powder is spherical, the particle size of the tungsten powder is 0.5-10 μm, and the mass ratio is 29.7-52.7%. The present invention selects spherical tungsten powder because the spherical tungsten powder has good fluidity and compressibility, and is easy to distribute evenly; the gaps between spherical particles are small, which is conducive to the preparation of a denser tungsten-based composite material; there are fewer contact points between spherical particles, which reduces stress concentration during sintering and can obtain a more uniform sintered body.
[0016] The present invention also provides a method for preparing a high-strength and toughness tungsten-based composite material, such as Figure 1 As shown, the following steps are included:
[0017] Step 1: Place tungsten powder and nanoparticles in a ball mill under inert gas protection for high-energy ball grinding;
[0018] Step 2: placing the main branch fibers, branch fibers and bridging fibers in anhydrous ethanol for ultrasonic cleaning, and vacuum drying; spraying the branch fibers on the main branch fibers by electrostatic spraying to form a branch structure;
[0019] Step 3: Place the pre-treated branched structure and bridging fiber in step 2 into a three-dimensional powder mixer for preliminary mixing to form a multi-endpoint network-like structure;
[0020] Step 4: Fill the tungsten powder and nanoparticles processed in step 1 into the mold of the multi-endpoint quasi-net structure constructed in step 3, and compact them by cold isostatic pressing to form a green body;
[0021] Step 5: Place the green body formed in step 4 into a sintering furnace equipped with an electromagnetic coil. When the set temperature is reached, vacuum sintering is performed under variable magnetic field conditions. After cooling, demolding is performed to obtain a high-strength and toughness tungsten-based composite material.
[0022] Preferably, in step 1, the inert gas is argon; the mass ratio of the grinding balls to the tungsten powder during ball grinding is 5 to 35:1; the rotation speed of the ball mill is 260 to 640 r / min, and the ball milling time is 6 to 18 hours. The present invention uses a high-energy ball grinding method, which can break the agglomeration phenomenon between the nanoparticles through high-energy collisions and shear forces during the ball milling process, so that the nanoparticles are evenly dispersed in the matrix of the tungsten powder. During the ball milling process, the surfaces of the nanoparticles and tungsten powder will be mechanically activated to produce a large amount of fresh surfaces, which increases the surface activity of the two and thus enhances the interfacial bonding force. Ball milling under the protection of argon can isolate oxygen and moisture, prevent tungsten powder and nanoparticles from undergoing oxidation reactions during the ball milling process, and ensure the purity of the material.
[0023] Preferably, in step 2, the ultrasonic cleaning time is 5 to 20 minutes; the vacuum drying time is 15 to 30 minutes; during the electrostatic spraying process, the voltage used is between 30kV and 60kV, and the spraying distance is 15 to 60cm. Ultrasonic cleaning of the surface of tungsten fiber and alumina fiber can effectively remove grease, dust and other contaminants on the fiber surface; the ultrasonic action can also penetrate into the tiny gaps and holes on the fiber surface, remove hard-to-reach contaminants, and remove the oxide layer on the fiber surface, making the fiber more active. Electrostatic spraying uses the action of electrostatic force to spray the branch fibers onto the main branch fibers. Due to the action of electrostatic force, the branch fibers can be evenly dispersed on the main branch fibers to avoid agglomeration. Electrostatic spraying can achieve a good coverage effect and ensure that the branch fibers are fully covered on the main branch fibers.
[0024] Preferably, in step 3, the mixing time is 3 to 5 hours, and the mixing speed is 100 to 300 r / min.
[0025] Preferably, in step 4, a hydraulic press is used for cold isostatic pressing, and the cold pressing pressure is 150 to 300 MPa.
[0026] Preferably, in step 5, the sintering pressure is 100-200 MPa, the set temperature is 1000-1300°C; the variable magnetic field is generated by an alternating current, the voltage provided is 220V-380V, the frequency is 300-600Hz, and the time is 0.5-3h. By changing the voltage and frequency of the electromagnetic coil, a variable magnetic field is generated, so that the magnetic nanoparticles in the composite material change accordingly.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The main branch fiber is the basic skeleton in the toughening unit. When the tungsten-based composite material is subjected to stress, it can rely on the high strength and high modulus characteristics of the fiber itself to transfer the stress from one end to the other end. In addition, the main branch fiber is made of long tungsten fiber, which can carry more loads, and the stress transfer path is longer, consuming more energy.
[0029] (2) The branch fibers are distributed on the main branch fibers by electrostatic spraying to form a branched structure. This structure makes the crack propagation path more complex and diverse, further dispersing and bearing stress; the branch fibers can also play a bridging role near the crack tip to prevent further crack expansion.
[0030] (3) The main branch fibers are connected to each other through bridging fibers, forming a more stable and strong multi-endpoint mesh structure. Alumina fibers have high strength and good thermal stability, which not only increases the connection between the main branch fibers, but also provides an additional energy absorption mechanism. When the material is under stress, the bridging fibers can also transfer the load and play a bridging role when the crack propagates, delaying the expansion of the crack. At low temperatures, especially below 550°C, the mass and volume of alumina fibers will shrink sharply, with a shrinkage rate of more than 85%. However, as the temperature continues to rise, this shrinkage trend will gradually weaken and remain stable at higher temperatures, thereby generating certain gaps around the alumina fibers. These gaps can provide a good buffer space when the composite material is under stress, thereby consuming energy and improving toughness.
[0031] (4) Nanoparticles can act as heterogeneous nucleation sites due to their high specific surface area and high surface energy, promoting the grain refinement of the matrix material. Fine grains can improve the hardness and strength of the material; nanoparticles can prevent crack propagation through the pinning effect, thereby improving the fracture toughness of the material. When a crack encounters a nanoparticle, the particle will pin the crack tip like a nail, consuming more energy to expand the crack. When magnetic nanoparticles are mixed with non-magnetic nanoparticles, the magnetic nanoparticles can continuously arrange their magnetic moments under a variable magnetic field, thereby forming multiple tiny channels between the non-magnetic nanoparticles. When the tungsten-based composite material is subjected to stress, the gaps formed by these tiny channels can absorb and consume part of the stress well, rather than just dispersing the stress. In addition, the existence of tiny channels provides additional space for the composite material to produce volume changes due to thermal expansion and contraction during high-temperature sintering and low-temperature cooling, reducing the internal stress concentration problem caused by thermal stress, improving the thermal shock resistance of the composite material, and extending its service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a flow chart for preparing high-strength and toughness tungsten-based composite materials. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention are described in detail below, and the described embodiments are only some embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention. The present invention is further described below in conjunction with specific embodiments.
[0034] Unless otherwise specified, the experimental materials and reagents used in the following examples can be obtained from commercial sources.
[0035] Example 1
[0036] This embodiment provides a high-strength and toughness tungsten-based composite material, in which the main branch fiber is a long tungsten fiber with a length of 32 mm and a diameter of 150 μm, accounting for 30% by mass; the branch fiber is a short tungsten fiber with a length of 2 mm and a diameter of 55 μm, accounting for 8% by mass; the bridging fiber is an alumina fiber with a length of 22 mm and a diameter of 120 μm, accounting for 16% by mass; the non-magnetic nanoparticles are TiC with a particle size of 50 nm, accounting for 0.5% by mass; the non-magnetic nanoparticles are nickel nanoparticles with a particle size of 15 nm, accounting for 0.2% by mass; the particle size of the tungsten powder is 10 μm, accounting for 45.3% by mass.
[0037] The specific preparation method is as follows:
[0038] Step 1: Put tungsten powder, TiC nanoparticles and nickel nanoparticles into a ball mill under argon protection for high-energy ball grinding. The mass ratio of grinding balls to tungsten powder is 15:1, the speed of the ball mill is 360r / min, and the ball milling time is 10h.
[0039] Step 2: Place the long tungsten fiber, short tungsten fiber and alumina fiber in anhydrous ethanol for ultrasonic cleaning for 15 minutes and vacuum dry for 25 minutes; use electrostatic spraying to spray the short tungsten fiber on the long tungsten fiber to form a dendrite structure, the voltage is 56 kV, and the spraying distance is 32 cm;
[0040] Step 3: Place the pretreated dendritic structure and alumina fiber in step 2 into a three-dimensional powder mixer for preliminary mixing for 5 hours at a mixing speed of 200 r / min to form a primary fiber network structure;
[0041] Step 4: Fill the tungsten powder, TiC nanoparticles and nickel nanoparticles processed in step 1 into the mold of the primary fiber network constructed in step 3, and use a hydraulic press to perform cold isostatic pressing at a cold pressing pressure of 200 MPa to compact it to form a green body;
[0042] Step 5: Place the green body formed in step 4 into a sintering furnace equipped with an electromagnetic coil. When the temperature reaches 1300°C, turn on the alternating current with a voltage of 220V and a frequency of 500Hz, and perform vacuum sintering. Uniformly apply pressure to 120MPa and sinter for 2h. After cooling, demold the sample to obtain a high-strength and toughness tungsten-based composite material.
[0043] Example 2
[0044] This embodiment provides a high-strength and toughness tungsten-based composite material, in which the main branch fiber is a long tungsten fiber with a length of 27 mm and a diameter of 120 μm, accounting for 28% by mass; the branch fiber is a short tungsten fiber with a length of 3 mm and a diameter of 50 μm, accounting for 10% by mass; the bridging fiber is an alumina fiber with a length of 28 mm and a diameter of 100 μm, accounting for 15% by mass; the nanoparticles are TiC with a particle size of 60 nm, accounting for 0.6% by mass; the non-magnetic nanoparticles are nickel nanoparticles with a particle size of 10 nm, accounting for 0.3% by mass; the particle size of the tungsten powder is 3.5 μm, accounting for 46.1% by mass.
[0045] The specific preparation method is as follows:
[0046] Step 1: Put tungsten powder, TiC nanoparticles and nickel nanoparticles into a ball mill under argon protection for high-energy ball grinding. The mass ratio of grinding balls to tungsten powder is 25:1, the speed of the ball mill is 260r / min, and the ball milling time is 6h.
[0047] Step 2: Place the long tungsten fiber, short tungsten fiber and alumina fiber in anhydrous ethanol for ultrasonic cleaning for 5 minutes and vacuum dry for 15 minutes; use electrostatic spraying to spray the short tungsten fiber on the long tungsten fiber to form a dendrite structure, the voltage is 30 kV, and the spraying distance is 15 cm;
[0048] Step 3: Place the pretreated dendritic structure and alumina fiber in step 2 into a three-dimensional powder mixer for preliminary mixing for 3 hours at a mixing speed of 100 r / min to form a primary fiber network structure;
[0049] Step 4: Fill the tungsten powder, TiC nanoparticles and nickel nanoparticles processed in step 1 into the mold of the primary fiber network constructed in step 3, and use a hydraulic press to perform cold isostatic pressing at a cold pressing pressure of 150 MPa to compact it to form a green body;
[0050] Step 5: Place the green body formed in step 4 into a sintering furnace equipped with an electromagnetic coil. When the temperature reaches 1000°C, turn on the alternating current with a voltage of 300V and a frequency of 300Hz, and perform vacuum sintering. Uniformly apply pressure to 100MPa and sinter for 0.5h. After cooling, demold the sample to obtain a high-strength and toughness tungsten-based composite material.
[0051] Example 3
[0052] This embodiment provides a high-strength and toughness tungsten-based composite material, in which the main branch fiber is a long tungsten fiber with a length of 50 mm and a diameter of 180 μm, accounting for 36% by mass; the branch fiber is a short tungsten fiber with a length of 1.5 mm and a diameter of 100 μm, accounting for 12% by mass; the bridging fiber is an alumina fiber with a length of 20 mm and a diameter of 200 μm, accounting for 20% by mass; the nanoparticles are ZrC with a particle size of 35 nm, accounting for 1.8% by mass; the non-magnetic nanoparticles are nickel nanoparticles with a particle size of 20 nm, accounting for 0.5% by mass; the particle size of the tungsten powder is 0.5 μm, accounting for 29.7% by mass.
[0053] The specific preparation method is as follows:
[0054] Step 1: Put tungsten powder, ZrC nanoparticles and nickel nanoparticles into a ball mill under argon protection for high-energy ball grinding. The mass ratio of grinding balls to tungsten powder is 35:1, the speed of the ball mill is 640r / min, and the ball milling time is 12h.
[0055] Step 2: Place the long tungsten fiber, short tungsten fiber and alumina fiber in anhydrous ethanol for ultrasonic cleaning for 20 minutes and vacuum dry for 30 minutes; use electrostatic spraying to spray the short tungsten fiber on the long tungsten fiber to form a dendrite structure, the voltage is 60kV, and the spraying distance is 60cm;
[0056] Step 3: Place the pretreated dendritic structure and alumina fiber in step 2 into a three-dimensional powder mixer for preliminary mixing for 4.5 hours at a mixing speed of 300 r / min to form a primary fiber network structure;
[0057] Step 4: Fill the tungsten powder, ZrC nanoparticles and nickel nanoparticles processed in step 1 into the mold of the primary fiber network constructed in step 3, and use a hydraulic press to perform cold isostatic pressing at a cold pressing pressure of 300 MPa to compact it to form a green body;
[0058] Step 5: Place the green body formed in step 4 into a sintering furnace equipped with an electromagnetic coil. When the temperature reaches 1100°C, turn on the alternating current with a voltage of 380V and a frequency of 600Hz. Perform vacuum sintering and uniformly pressurize to 200MPa. Sinter for 3h. After cooling, demold the sample to obtain a high-strength and toughness tungsten-based composite material.
[0059] Example 4
[0060] This embodiment provides a high-strength and toughness tungsten-based composite material, in which the main branch fiber is a long tungsten fiber with a length of 10 mm and a diameter of 80 μm, accounting for 24% by mass; the branch fiber is a short tungsten fiber with a length of 1 mm and a diameter of 30 μm, accounting for 8% by mass; the bridging fiber is an alumina fiber with a length of 16 mm and a diameter of 50 μm, accounting for 15% by mass, the nanoparticles are ZrC with a particle size of 25 nm, accounting for 0.2% by mass; the non-magnetic nanoparticles are nickel nanoparticles with a particle size of 18 nm, accounting for 0.1% by mass; the particle size of the tungsten powder is 2.5 μm, accounting for 52.7% by mass.
[0061] The specific preparation method is as follows:
[0062] Step 1: Put tungsten powder, ZrC nanoparticles and nickel nanoparticles into a ball mill under argon protection for high-energy ball grinding. The mass ratio of grinding balls to tungsten powder is 5:1, the speed of the ball mill is 460r / min, and the ball milling time is 18h.
[0063] Step 2: Place the long tungsten fiber, short tungsten fiber and alumina fiber in anhydrous ethanol for ultrasonic cleaning for 12 minutes and vacuum dry for 18 minutes; use electrostatic spraying to spray the short tungsten fiber on the long tungsten fiber to form a dendrite structure, the voltage is 45kV, and the spraying distance is 26cm;
[0064] Step 3: Place the pretreated dendritic structure and alumina fiber in step 2 into a three-dimensional powder mixer for preliminary mixing for 3.5 hours at a mixing speed of 220 r / min to form a primary fiber network structure;
[0065] Step 4: Fill the tungsten powder, ZrC nanoparticles and nickel nanoparticles processed in step 1 into the mold of the primary fiber network constructed in step 3, and use a hydraulic press to perform cold isostatic pressing at a cold pressing pressure of 220 MPa to compact them to form a green body;
[0066] Step 5: Place the green body formed in step 4 into a sintering furnace equipped with an electromagnetic coil. When the temperature reaches 1150°C, turn on the alternating current with a voltage of 360V and a frequency of 560Hz, and perform vacuum sintering. Uniformly apply pressure to 180MPa and sinter for 1.5h. After cooling, demold the sample to obtain a high-strength and toughness tungsten-based composite material.
[0067] Example 5
[0068] This embodiment provides a high-strength and toughness tungsten-based composite material, wherein the main branch fiber is a long tungsten fiber with a length of 40 mm and a diameter of 300 μm, accounting for 31% by mass; the branch fiber is a short tungsten fiber with a length of 2.2 mm and a diameter of 15 μm, accounting for 11% by mass; the bridging fiber is an alumina fiber with a length of 20 mm and a diameter of 160 μm, accounting for 18% by mass; the nanoparticles are Al2O3 with a particle size of 36 nm. 2 O 3 , accounting for 1.5% by mass; the non-magnetic nanoparticles are nickel nanoparticles with a particle size of 12nm, accounting for 0.4% by mass; the particle size of tungsten powder is 1.6μm, accounting for 38.1% by mass.
[0069] The specific preparation method is as follows:
[0070] Step 1: Mix tungsten powder, Al 2 O 3 The nanoparticles and nickel nanoparticles were placed in a ball mill under argon protection for high-energy ball grinding. The mass ratio of the grinding balls to the tungsten powder during ball grinding was 28:1, the speed of the ball mill was 380 r / min, and the ball milling time was 14 h.
[0071] Step 2: Place the long tungsten fiber, short tungsten fiber and alumina fiber in anhydrous ethanol for ultrasonic cleaning for 16 minutes and vacuum dry for 19 minutes; use electrostatic spraying to spray the short tungsten fiber on the long tungsten fiber to form a dendrite structure, the voltage is 41 kV, and the spraying distance is 32 cm;
[0072] Step 3: Place the pretreated dendritic structure and alumina fiber in step 2 into a three-dimensional powder mixer for preliminary mixing for 4.2 hours at a mixing speed of 260 r / min to form a primary fiber network structure;
[0073] Step 4: Take the tungsten powder and Al 2 O 3 The nanoparticles and nickel nanoparticles are filled into the mold of the primary fiber network constructed in step 3, and a hydraulic press is used to perform cold isostatic pressing at a cold pressing pressure of 290 MPa to compact it to form a green body;
[0074] Step 5: Place the green body formed in step 4 into a sintering furnace equipped with an electromagnetic coil. When the temperature reaches 1250°C, turn on the alternating current with a voltage of 250V and a frequency of 460Hz, and perform vacuum sintering. Uniformly apply pressure to 160MPa and sinter for 2.5h. After cooling, demold the sample to obtain a high-strength and toughness tungsten-based composite material.
[0075] Example 6
[0076] This embodiment provides a high-strength and toughness tungsten-based composite material, wherein the main branch fiber is a long tungsten fiber with a length of 28 mm and a diameter of 220 μm, accounting for 25% by mass; the branch fiber is a short tungsten fiber with a length of 2.2 mm and a diameter of 85 μm, accounting for 11% by mass; the bridging fiber is an alumina fiber with a length of 24 mm and a diameter of 140 μm, accounting for 16% by mass; the nanoparticles are Al2O3 with a particle size of 40 nm. 2 O 3 , accounting for 0.3% by mass; the non-magnetic nanoparticles are nickel nanoparticles with a particle size of 16nm, accounting for 0.15% by mass; the particle size of tungsten powder is 4.8μm, accounting for 47.55% by mass.
[0077] The specific preparation method is as follows:
[0078] Step 1: Mix tungsten powder, Al 2 O 3 The nanoparticles and nickel nanoparticles were placed in a ball mill under argon protection for high-energy ball grinding. The mass ratio of the grinding balls to the tungsten powder during ball grinding was 30:1, the speed of the ball mill was 460 r / min, and the ball milling time was 17 h.
[0079] Step 2: Place the long tungsten fiber, short tungsten fiber and alumina fiber in anhydrous ethanol for ultrasonic cleaning for 8 minutes and vacuum dry for 24 minutes; use electrostatic spraying to spray the short tungsten fiber on the long tungsten fiber to form a dendrite structure, the voltage is 38kV, and the spraying distance is 20cm;
[0080] Step 3: Place the pretreated dendritic structure and alumina fiber in step 2 into a three-dimensional powder mixer for preliminary mixing for 3.8 hours at a mixing speed of 1900 r / min to form a primary fiber network structure;
[0081] Step 4: Take the tungsten powder and Al 2 O 3 Nanoparticles and nickel nanoparticles are filled into the mold of the primary fiber network constructed in step 3, and cold isostatic pressing is performed using a hydraulic press with a cold pressing pressure of 1800 MPa to compact it to form a green body;
[0082] Step 5: Place the green body formed in step 4 into a sintering furnace equipped with an electromagnetic coil. When the temperature reaches 1190°C, turn on the alternating current with a voltage of 290V and a frequency of 470Hz. Perform vacuum sintering and uniformly pressurize to 140MPa. Sinter for 0.8h. After cooling, demold the sample to obtain a high-strength and toughness tungsten-based composite material.
[0083] Comparative Example 1
[0084] This comparative example provides a method for preparing a high-strength and high-toughness tungsten-based composite material. Except for not containing branched fibers, the remaining steps are the same as those of Example 1.
[0085] Comparative Example 2
[0086] This comparative example provides a method for preparing a high-strength and high-toughness tungsten-based composite material. Except for not containing bridging fibers, the remaining steps are the same as those of Example 1.
[0087] Comparative Example 3
[0088] This comparative example provides a method for preparing a high-strength and toughness tungsten-based composite material. Except for not containing nanoparticles, the remaining steps are the same as those of Example 1.
[0089] The products prepared in Examples 1-6 and the products prepared in Comparative Examples 1-3 were subjected to bending tests according to GB / T 232-2010 “Metallic Material Bending Test Methods”. The tensile strength and tensile strain results are shown in Table 1.
[0090] Table 1 Mechanical properties of tungsten-based composite materials of Examples 1-6 and Comparative Examples 1-3
[0091] Tensile strength(MPa) Tensile strain (%) Example 1 1530 3.06 Example 2 1260 2.56 Example 3 1158 1.97 Example 4 1196 2.47 Example 5 1023 1.34 Example 6 1206 1.85 Comparative Example 1 985 0.95 Comparative Example 2 873 0.71 Comparative Example 3 965 0.89
[0092] Tensile strength and tensile strain are important indicators for evaluating the mechanical properties of tungsten-based composite materials. Tensile strength refers to the maximum stress that a composite material can withstand during stretching. Tensile strain refers to the amount of deformation that occurs in a composite material during stretching, expressed as a percentage, to reflect the plastic deformation ability of the composite material during stretching. From Table 1, it can be seen that the tensile strength of Examples 1 to 6 provided by the present invention is 1023 to 1530 MPa, which is significantly higher than 873 to 985 MPa of Comparative Examples 1 to 3, indicating that the tensile strength of the tungsten-based composite material containing toughening units composed of main branch fibers, branch fibers, bridging fibers and nanoparticles is significantly improved, and has higher strength. In the embodiments provided by the present invention, the highest tensile strain is 3.06% and the lowest is 1.34%, while in the comparative example, the highest tensile strain value is only 0.95%. The tensile strain value of the composite material in the embodiments is significantly better than that in the comparative example, indicating that the tungsten-based composite material containing toughening units composed of main branch fibers, branch fibers, bridging fibers and nanoparticles has better toughness and good microstructure, and can undergo greater plastic deformation during the deformation of the tungsten-based composite material, thereby having a higher tensile strain.
[0093] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-strength and toughness tungsten-based composite material, characterized in that: It includes a multi-end point reticular structure, nanoparticles and a matrix material; the multi-end point reticular structure includes main branch fibers, branch fibers and bridging fibers; in the multi-end point reticular structure, adjacent main branch fibers are interconnected by bridging fibers, and the branch fibers are distributed on the main branch fibers; the nanoparticles include non-magnetic nanoparticles and magnetic nanoparticles, all of which are uniformly distributed in the multi-end point reticular structure; the matrix material is tungsten powder.
2. A high-strength and toughness tungsten-based composite material according to claim 1, characterized in that: The main branch fiber is a long tungsten fiber with a length of 10 to 50 mm, a diameter of 80 to 300 μm, and a mass proportion of 24 to 36%; the branch fiber is a short tungsten fiber with a length of 1 to 3 mm, a diameter of 30 to 100 μm, and a mass proportion of 8 to 12%; the bridging fiber is an alumina fiber with a fiber length of 16 to 28 mm, a diameter of 50 to 200 μm, and a mass proportion of 15 to 20%.
3. The high-strength and toughness tungsten-based composite material according to claim 1, characterized in that: The non-magnetic nanoparticles are any one of Al2O3 nanoparticles, ZrC nanoparticles and TiC nanoparticles; the particle size of the nanoparticles is 25-60nm, and the mass proportion is 0.2-1.8%; the magnetic nanoparticles are nickel nanoparticles, and the particle size of the nickel nanoparticles is 10-20nm, and the mass proportion is 0.1-0.5%.
4. The high-strength and toughness tungsten-based composite material according to claim 1, characterized in that: The tungsten powder is in a spherical shape, has a particle size of 0.5 to 10 μm, and accounts for 29.7 to 52.7% by mass.
5. A method for preparing a high-strength and toughness tungsten-based composite material according to any one of claims 1 to 4, characterized in that: The steps include: Step 1: Place tungsten powder and nanoparticles in a ball mill under inert gas protection for high-energy ball grinding; Step 2: placing the main branch fibers, branch fibers and bridging fibers in anhydrous ethanol for ultrasonic cleaning, and vacuum drying; spraying the branch fibers on the main branch fibers by electrostatic spraying to form a branch structure; Step 3: Place the pre-treated dendritic structure and bridging fibers in step 2 into a three-dimensional powder mixer for preliminary mixing. Form a multi-endpoint mesh structure; Step 4: Fill the tungsten powder and nanoparticles processed in step 1 into the mold of the multi-endpoint quasi-net structure constructed in step 3, and compact them by cold isostatic pressing to form a green body; Step 5: Place the green body formed in step 4 into a sintering furnace equipped with an electromagnetic coil. When the set temperature is reached, vacuum sintering is performed under variable magnetic field conditions. After cooling, demolding is performed to obtain a high-strength and toughness tungsten-based composite material.
6. The method for preparing a high-strength and toughness tungsten-based composite material according to claim 5, characterized in that: In step 1, the inert gas is argon; the mass ratio of grinding balls to tungsten powder during ball grinding is 5 to 35:1; the rotation speed of the ball mill is 260 to 640 r / min, and the ball milling time is 6 to 18 hours.
7. The method for preparing a high-strength and toughness tungsten-based composite material according to claim 5, characterized in that: In step 2, the ultrasonic cleaning time is 5 to 20 minutes; the vacuum drying time is 15 to 30 minutes; during the electrostatic spraying process, the voltage used is between 30 kV and 60 kV, and the spraying distance is 15 to 60 cm.
8. The method for preparing a high-strength and toughness tungsten-based composite material according to claim 5, characterized in that: In step 3, the mixing time is 3 to 5 hours, and the mixing speed is 100 to 300 r / min.
9. The method for preparing a high-strength and toughness tungsten-based composite material according to claim 5, characterized in that: In the step 4, a hydraulic press is used for cold isostatic pressing, and the cold pressing pressure is 150 to 300 MPa.
10. The method for preparing a high-strength and toughness tungsten-based composite material according to claim 5, characterized in that: In step 5, the sintering pressure is 100-200 MPa, the set temperature is 1000-1300° C.; the variable magnetic field is generated by an alternating current, the voltage provided is 220V-380V, the frequency is 300-600Hz, and the time is 0.5-3h.
Citation Information
Patent Citations
A layered fiber toughening tungsten-based composite material and its preparation method
CN112442643B
Layered fiber toughened tungsten-based composite material and preparation method thereof
CN112442643A
Method for preparing large-size tungsten fiber toughened tungsten Wf / W composite material
CN113953510A
Tungsten-based composite material synergistically toughened by tungsten fibers and oxide nanoparticles and preparation method of tungsten-based composite material
CN114959518A
Preparation method of superfine tungsten alloy material
CN115505772A